The need of practical teaching in vocational high school of Automation and Office Management Program - Febrika Yogie Hermanto; Sutirman Sutirman; Berlina Hidayati; Mar'atus Sholikah (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2019)
The success of vocational education cannot be separated from the proper management of learning by its objectives. This study aims to explore the pitfalls and the needs of practical teaching in the Vocational High School of Automation and Office Management Program (AOMP) in Yogyakarta city. This research uses a descriptive method with a qualitative approach. The data obtained were analyzed by using the qualitative analysis model of Miles and Huberman with stages: data reduction, presenting data, verifying data, and concluding data. The results of this study show that the complex equations that are occurred in practical learning of the Vocational High School of AOMP are including the absence of practical teaching materials that are relevant to the industry, there is no specific time for practical learning, lack of facilities and infrastructures, deficiency tools and time to use office laboratories, and there are new types of jobs in the office workforce that are difficult to be followed. Moreover, these matters are complicated for schools to be embodied in the form of practical learning, resulting in poorly trained vocational students in doing their duty that fit the areas of expertise learned. This hardship implies that vocational students become less confident in doing their jobs in the industry either during an internship program or when working in the industry. This research is limited to pitfalls that occur in Yogyakarta City and in schools, which are the subject of this research.